Determinants of and barriers to people's financial inclusion in Mexico - Cassimon, Steven (OECD Publishing, 2022)
Individuals' access to finance is particularly low in Mexico. Widening access to finance would boost growth and inclusion. This paper uses microdata from the National Survey for Financial Inclusion to assess the drivers of and the barriers to people's financial inclusion in Mexico. Results show that working in the formal sector, the level of wealth and income, educational attainment, and age are the socio-economic characteristics that most affect the likelihood of holding any formal financial product. The relative importance of these characteristics, however, varies across financial products. Economic barriers to individuals' financial inclusion are strongly associated with widespread informality and a low level of education and income. These results suggest that financial education programmes and credit registries considering a wider set of data to assess informal workers' credit worthiness would be promising avenues to help more Mexicans access financial services
Keywords: Economics; Mexico